Pengaruh Pemberian Jus Mentimun Air Kelapa Muda Terhadap Penurunan Tekanan Darah Lansia Hipertensi Di Panti Sosial Tresna Werdha “PUSPAKARMA” Mataram - Nimade Dwi Anjani; Niketut Sri Sulendri; Yuli Laraeni; Iketut Swirya Jaya (Poltekkes Kemenkes Mataram, 2017)
Background. Hypertension or high blood pressure is an increase in systolic blood pressure equal to or greater than 140 mmHg and diastolic blood pressure is equal to or greater than 90 mmHg. Hypertension often occurs in elderly considering almost most of the function of the organs began to decline with age. Cucumber and coconut water contain high enough potassium which can help lower blood pressure. Combination of juice of young coconut cucumber water can increase potassium input in the body so it can lower blood pressure, especially in elderly group. Research Purposes. This study aims to determine the effect of young coconut water cucumber juice on the decrease in hypertensive blood pressure at the Social Institution Tresna Werdha